Research regardind to the improvement and optimisation of soil conservation system "no tillage" for wheat culture, specific pedo-climatic conditions of the Transylvania plain area - Felicia Cheţan; Cornel Cheţan; Alina Şimon (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
Production data registered at winter wheat Ariesan cultivar in 2007-2017 period, indicates suitability for cultivation in system with no ploughing, the difference in production between the two systems classic and conservative is just 81 kg/ha thus, in the classic system the average yield was 5671 kg/ha and in "no tillage" system 5590 kg/ha. Application of "no tillage" system at wheat culture requires a fuel consumption of 34.8 l/ha at the price 181 lei/ha compared with the classical technology which consumed 77 l/ha at the price 404 lei/ha, the economy achieved in 223 lei/ha in favor of "no tillage" system.
Keywords: Q01; Q15; Q16; 330; direct seeding; clime; yield; efficiency; wheat